A framework for performance analysis of OpenStreetMap data in navigation applications: the case of a well-developed road network in Australia - Reza Hosseini; Daoqin Tong; Samsung Lim; Gunho Sohn; Győző Gidófalvi (Annals of GIS)
Although much effort has been put into assessing and improving OpenStreetMap (OSM) data quality, further research is required to determine its reliability and robustness for real-world applications. This study introduces a framework, built on open-source geospatial tools, for analysing the performance of OSM road data across different navigation applications. We tested this framework on an extensive 41,000 km road network in Australia. While our findings generally supported the quality of the OSM dataset, analyses of census data revealed two key relationships: first, a significant link between a city’s population and the quality of its OSM data, and second, a strong influence of Information and Communications Technology (ICT) infrastructure on OSM data development. Furthermore, while navigation tests showed that OSM road networks performed reasonably well, scenario analyses highlighted several issues: a strong correlation between data quality and navigation accuracy; a negative impact of distance on OSM-based route accuracy for long inner- and inter-city routes due to accumulated errors; and the tendency of OSM to suggest sub-optimal paths for routes to isolated locations. This framework offers valuable benefits to a wide range of users. The OSM community can use it to assess data quality before application; individuals and businesses can easily evaluate its utility for navigation and route-planning; and local governments can benefit from improved quality control, particularly for projects involving Connected and Automated Vehicles (CAVs). Finally, the framework’s capacity to design and analyse various routing scenarios provides new insights into overall road network quality.